Penilaian Kecerdasan Spiritual Sebagai Pendekatan Interdisipliner Dalam Pendidikan Islam - Abd. Rahman Saleh; Andi Fitriani Djollong; Muhammad Ikhwan Ahmad; Suherni Suherni; Sukriati (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
Spiritual intelligence is a crucial dimension in shaping students' character and personality, balancing intellectual, emotional, and spiritual aspects. In the context of Islamic education, assessing spiritual intelligence serves as a strategic instrument for measuring the success of a learning process that focuses not only on cognition but also on values ​​of faith, morality, and social sensitivity. This study, a literature review, aims to examine the concept of assessing spiritual intelligence as an interdisciplinary approach in Islamic education. The analysis was conducted through a review of various current scientific sources related to spiritual intelligence theory, interdisciplinary paradigms, and principles of Islamic educational evaluation. The results indicate that assessing spiritual intelligence can be conducted through the integration of psychological, educational, and Islamic theological dimensions, prioritizing affective, reflective, and contextual approaches. The application of this assessment model encourages students to internalize Islamic values ​​in real life. Thus, assessing spiritual intelligence serves not merely as a measuring tool but also as a means of fostering students' character and spirituality. This study recommends the development of an interdisciplinary assessment instrument oriented toward the formation of a perfect human being in modern Islamic education.